Pricing feeder pigs - J H McCoy; R V Price; M L Manuel; C E Ward (Kansas Agricultural Experiment Station Research Reports, 1975)
Recent increases in specialized production of feeder pigs has stimulated interest in various methods of pricing pigs outside traditional marketing channels. Most such methods are either negotiated pricing or formula pricing. In privately negotiated transactions, both seller and buyer must have approximately equal knowledge of markets and of grade and weight characteristics of the pigs. In addition, each should have about equal bargaining ability.; Swine Day, Manhattan, KS, November 13, 1975
Keywords: Swine day; 1975; Kansas Agricultural Experiment Station contribution; no. 505; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 283; Swine; Feeder hogs; Weight; Grade characteristics